The ‘Double-Faced’ Legal Expression: Dynamics and Legal Loopholes in Interfaith Marriages in Indonesia - Rajafi, Ahmad; Sugitanata, Arif; Lusiana, Vinna (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
Interfaith marriages remain a controversial subject among scholars in Indonesia. Despite the legal prohibition, the practice of interfaith marriage continues to persist. This article analyses various legal norms, decisions of the state courts and the Indonesian Constitutional Court related to interfaith marriages, revealing disparities between legal norms and practical implementation. Employing a normative approach through a literature review, this research finds that the state legislation strictly prohibits interfaith marriage. Paradoxically, couples navigate a legal workaround, exploiting a loophole in Population Administration Law No. 23 of 2006 to formalise their marriages. They submit applications to the district court, and the court’s decisions serve as the basis for recording their union. Some couples also employ an alternative strategy by marrying abroad and subsequently registering their unions upon returning to Indonesia. The article argues that the state’s legal expression in regulating the practice of interfaith marriages in Indonesia manifests ‘double face’. This study holds significant implications, particularly in enhancing policy comprehension, providing profound insights into the legal dynamics of interfaith marriages in Indonesia, and assessing its impact on citizens’ religious freedom. [Perkawinan beda agama di Indonesia masih menjadi isu kontroversial di kalangan para sarjana. Meskipun hukum negara telah melarangnya, praktik perkawinan beda agama masih terus berjalan hingga saat ini. Artikel ini menganalisis sejumlah hukum negara, putusan Pengadilan Negeri, dan putusan Mahkamah Konstitusi terkait perkawinan beda agama di Indonesia, mengungkap disparitas antara aturan hukum dan praktik. Menggunakan penelitian kepustakaan dengan pendekatan normatif, penelitian ini menemukan bahwa hukum negara telah mengatur secara ketat perkawinan beda agama dengan melarangnya. Namun, para pasangan beda agama memanfaatkan celah hukum dalam Undang-Undang No. 23 Tahun 2006 tentang Administrasi Kependudukan untuk mencatatkan perkawinan mereka. Mereka mengajukan permohonan ke pengadilan negeri dan ketetapannya digunakan sebagai dasar untuk mencatatkan perkawinan mereka. Sebagian dari mereka juga memanfaat “pintu belakang” dengan menikah di luar Indonesia dan kembali untuk mencatatkan administrasi perkawinan mereka. Dengan demikian, tulisan ini berpendapat bahwa ekspresi hukum negara dalam mengatur praktik perkawinan beda agama di Indonesia mencerminkan “dua wajah”. Kajian ini memiliki implikasi penting terutama dalam pemahaman kebijakan, memberikan wawasan mendalam tentang dinamika hukum perkawinan beda agama di Indonesia dan dampaknya terhadap kebebasan beragama bagi warga negara.]